1972
DOI: 10.1366/000370272774351705
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Wave-Length Modulation Device to Problems concerning Spectrometer Misalignment

Abstract: The use of wave-length modulation as a tool for minimizing spectrometer spectral misalignment is examined. A vibrating quartz plate is employed to repetitively scan a small wave-length interval at the exit slit of a spectrometer. Increased latitude is thereby provided for any slit or wave-length misalignment of the spectrometer, as long as the correct signal detection system is employed. Investigation of the effects of wave-length modulation on a typical line spectrum has revealed signal averaging as the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Refers to the bandpass of the interference filter (Narrow = 13 Á, Broad = 100 A). lyte line, the modulation pattern of the interfering line will differ from that of the analyte and can therefore be discriminated on the basis of phase or frequency (9). For example, a repetitive wavelength scan which is centered over the analyte line will produce an evenly spaced train of detected analyte peaks but would generate a slightly asymmetrical progression of interferant peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refers to the bandpass of the interference filter (Narrow = 13 Á, Broad = 100 A). lyte line, the modulation pattern of the interfering line will differ from that of the analyte and can therefore be discriminated on the basis of phase or frequency (9). For example, a repetitive wavelength scan which is centered over the analyte line will produce an evenly spaced train of detected analyte peaks but would generate a slightly asymmetrical progression of interferant peaks.…”
Section: Resultsmentioning
confidence: 99%
“…In wavelength modulation, the wavelength under observation by the photodetector is repetitively scanned at a predetermined frequency. In recent years, this technique has been employed in flame spectrometry to enable the use of continuum sources in atomic absorption (2-5), to reduce broad-band spectral interferences in flame spectrometry (6), to construct a pseudo-double-beam atomic absorption spectrometer (7), to carry out qualitative and quantitative flame emission spectrometry (8), and to correct and compensate for monochromator misalignment (9). In the present application, the modulation technique is employed to greatly reduce the effect of flame background or broad-band spectral interference on a detected flame emission signal.…”
mentioning
confidence: 99%
“…This integration time is important in both the spectral alignment procedure and the background correction cycle, particularly for weak emission lines. Hieftje and Sydor (36) concluded that signal averaging for 256 scans was essential for their sinusoidal demodulation step.…”
Section: Discussionmentioning
confidence: 99%
“…Quartz refractor plates have been incorporated in several previously described systems, typically to obtain derivative spectra during a wavelength scan with the use of lock-in amplifiers (25,26,(32)(33)(34)(35). Hieftje and Sydor (36) have examined the application of wavelength modulation to minimize spectrometer misalignment. A vibrating quartz plate was used to modulate the output wavelength and several demodulation approaches were analyzed and evaluated.…”
mentioning
confidence: 99%
“…18AT10/2, General Electric Co., Cleveland, Ohio). Detection of the reversed condition (indicating equality of the lamp and flame temperatures), as described by Snelleman (11), was simplified by use of a wavelength-modulated monochromator and synchronous detection system (12).…”
mentioning
confidence: 99%